Jenny Lind's America. - Cavanah, Frances (Philadelphia, Chilton Book Co., 1969)
A biography of the "Swedish Nightingale" whose vocal range and tone quality made her one of the leading opera stars of the mid-nineteenth century.
Keywords: Lind, Jenny, -- 1820-1887 -- Juvenile literature; Lind, Jenny, -- 1820-1887.